Making modern mothers : ethics and family planning in urban Greece - Paxson, Heather, 1968- (University of California Press, 2004)
Heather Paxson addresses the ambivalent perceptions of motherhood in Athens, as traditional views on femininity and childbearing are challenged by consumerism and imported biomedical family planning methods.
Keywords: Feminist anthropology -- Greece -- Athens.; Women -- Greece -- Athens -- Social conditions.; Motherhood -- Greece -- Athens.; Birth control -- Greece -- Athens -- Public opinion.; Public opinion -- Greece -- Athens.; Athens (Greece) -- Social life and customs.; Family planning services.; Abortion.; Gender identity.; Mothers.; Family Planning Services; Abortion, Legal; Gender Identity; Mothers; Sexual Behavior; Féminisme et anthropologie -- Grèce -- Athènes.; Femmes -- Grèce -- Athènes -- Conditions sociales.; Maternité -- Grèce -- Athènes.; Régulation des naissances -- Grèce -- Athènes -- Opinion publique.; Opinion publique -- Grèce -- Athènes.; Services de planification familiale.; Avortement.; Identité de genre.; Mères.; sex role.; mothers.; SOCIAL SCIENCE -- Feminism & Feminist Theory.; SOCIAL SCIENCE -- Gender Studies.; Gender identity; Family planning services; Abortion; Birth control -- Public opinion; Feminist anthropology; Manners and customs; Motherhood; Public opinion; Women -- Social conditions; Greece -- Athens; Feministische filosofie.; Moederschap.; Geboorteregeling.; Publieke opinie.